Utilization of recommended safe-landing strategies during falls in mountain biking - Rickie Ma; Freddie Kim; Sukhman Gosal; Gurvansh Mann; Stephen N. Robinovitch (Heliyon)
Falls are common in mountain biking (MTB), and often involve high speeds, large descent heights, and rough landing terrains. However, most falls in MTB do not cause serious injury. This may be due, in part, to protective movements used by MTB riders to avoid injury. Such “safe-landing strategies” are commonly discussed in the MTB community. However, studies have not synthesized or examined the validity of the recommended strategies. Our goal in this study was to determine whether riders utilize recommended safe-landing strategies during real-life falls in MTB. To address this goal, we identified 11 recommended safe-landing strategies through online content analysis and experienced MTB rider surveys. We then analyzed videos of 300 real-life MTB falls using a structured questionnaire to determine whether riders utilized the recommended strategies. The most commonly used strategies were upper limb bracing (58.3 %), elbow flexion at landing (48.0 %), stepping (47.0 %), knee flexion at landing (43.0 %), and bike separation (40.0 %). The least utilized strategies were reach-to-grasp (4.7 %), use of the arms to shield the face (6.3 %) and dismounting from the bike (6.7 %). Moderately utilized strategies included body rolling (26.7 %), neck rotation (26.7 %), and tucking (18.3 %). In 96 % of falls, rider utilized at least 1 recommended landing strategy. On average, riders utilized 3.04 (SD 1.6) recommended landing strategies when falling. Our results indicate that falls in MTB elicit common movement strategies that align with recommended techniques for avoiding injury during falls. Future research should examine the role of exercise in enhancing safe-landing responses and preventing injuries in MTB.